Geometric morphometrics to interpret the endophytic egg-laying behavior of Odonata (Insecta) from the Eocene of Patagonia, Argentina. (November 2019) - Romero-Lebrón, Eugenia; Gleiser, Raquel M.; Petrulevičius, Julián F.
Abstract: Although the order Odonata has a rich fossil record, many questions about its reproductive biology remain unanswered. There are two strategies of egg laying among odonates, exophytic and endophytic, the latter being one of the most revealing vestiges of plant–insect association in the fossil record. We assessed whether geometric morphometrics based on elliptical series of Fourier allow expression of variability of shape in traces of Odonata eggs within a leaf of Eucalyptus chubutensis (Berry) González (in part), González, 2009 (Myrtaceae) from Laguna del Hunco (Chubut, Argentina) (early Eocene) and whether this variability is consistent with the ichnotaxonomy of this material. We found that the largest variation corresponds to the compression of the shape while the remaining two components reflect variations in the apex position and its curvature, which changed according to the relative position of the traces in the leaf. There was no evidence that the hardness of the leaf would affect the shape of the egg trace. We postulate that these traces could have been produced by one single female: Variations in the pattern observable in the fossil of an originally three-dimensional structure are consistent with differences in the position of the eggs inserted by a single female who has flexed her abdomen to insert the eggs as she approaches the apex of the leaf (behavior observed also in extant dragonflies). For the first time, endophytic egg traces are analyzed with geometrical morphometrics, and this allows us to make inferences on the oviposition behavior of a female that lived around 52 million years ago.